Islamic accountability and waqf towards achieving equitable distribution of wealth within the Islamic economic framework - Hassan, Rusni; Salman, Syed Ahmed (International Research Centre of Islamic Economics and Finance (IRCIEF), International Islamic University College Selangor (KUIS, 2018)
The creation and distribution of wealth is a daily activity that we face. There are different ways and approaches in handling issues related to wealth. From the Islamic perspective, economic activities should be solved based on the Shari’ah. It is because we are indebted to Allah for bringing us into this existence and for entrusting us with the resources. Allah is the Creator of everything, including us. Hence, He is the absolute Owner while humans have only delegated ownership as the trustees of Allah. Since humans are not the real owners of the resources; rather they need to utilize the resources entrusted according to the will of the Allah. Humans are also accountable for any misuse of resources which is against the will of the real Owner. In order to discharge the responsibility as trustees of Allah in an accountable manner, humans need to meet the objective of Islamic economics, i.e. to achieve socio-economic justice. In addition, Islam encourages charity and donations, whereas waqf is one way of charity to show gratitude to Allah for what He has bestowed upon us. Waqf can fill the need of the society by providing free education, health services and others. It plays a significant role in achieving the objective of Islamic economy. Therefore, the aims of the paper are to highlight how economic problems are solved in the light of Shari’ah and to what extent waqf can play an important in uplifting the wellbeing of the society. The research method of this paper is based on library research. It is written solely based on secondary data, such as articles, books and online resources. This paper will be to the interest of researchers, donators, regulators and the public in general.